Administration of ethanol extract of Bajakah tampala (Spatholobus littoralis Hassk) stem decreased reactive oxygen species, visceral fat and body weight of obese rats - Vany Novanty; Wimpie Pangkahila; Ni Nyoman Ayu Dewi (Neurologico Spinale Medico Chirurgico, 2021)
Background: Oxidative stress plays a role in the obesity mechanism, thus leads to premature aging. High antioxidant capacity in Bajakah tampala stem may effectively lessen oxidative stress and reduce fat mass and body weight accordingly. This study aimed to provide Bajakah tampala stem extract's effect in lowering ROS level, visceral fat weight, and overall weight of obese male Wistar rats. Method: A true experimental design was conducted on male Wistar rats aged 2-3 months with obesity. Thirty-two obese rats were evenly divided into a placebo group and a group given Bajakah tampala stem extract, with 16 rats in each group. For 28 days, both groups were fed a high-fat diet. The subject body weights were weighed every week. ROS levels and visceral fat weight were evaluated after the intervention was done. Comparative analysis between groups was performed. Results: The results showed mean levels of ROS (56.2 ± 7.4 U/ml vs. 400.9 ± 50.7 U/ml; p < 0.001), visceral fat weight (2.6 ± 0.2 g vs. 3.4 ± 0.9 g; p < 0.001), and the final body weight (241.5 ± 2.8 g vs. 261.5 ± 13.8 g; p < 0.001) were significantly lower in the study group than the control group. Conclusion: The study indicates Bajakah tampala stem extract administration effectively reduced ROS levels, visceral fat weight, and body weight in obese male Wistar rats.